Характерні риси англійських ад’єктивних емосемізмів позитивної та негативної семантики - Melnychuk, Natalia (My University, 2021)
Nowadays much attention is paid to a person’s emotional factor in the language, because his everyday life can not be imagined without expression of emotions by means of a language. Therefore the focus of many linguistic studies is a person and his role in organizing and using the language as a means of communication. The anthropocentric nature of the modern linguistic paradigm determines the considerable interest of scientists in the problem of representation of emotions in the language and speech. That’s why the study of adjectives makes a particular interest, because they combine semantic and pragmatic components of the content (subject-logical and emotional-evaluative). Therefore the choice of an emotive adjective already reflects the speaker’s subjective attitude to the subject that he describes. A specific feature of adjectives is the combination of semantic and pragmatic plans of utterance in their structure which are reflected directly in their meanings (unlike other parts of speech in which these two aspects are not related and are implemented only in the utterance). Emotional component of Engish adjectival lexemes actualizes directly the subject’s positive or negative attitude to the object which he or she perceives. Emotions appear in two main categories, that’s why a certain kind of emotion has positive or negative colouring that expresses the speaker’s emotional attitude to the subjects. A significant complication of their semantic structure and the appearance of derived meanings make emotive adjectives extremely difficult to study. The article describes the semantic specialization of adjectival units caused by the potential communicative function in them which determines the predominance in their meanings of such elements as emotive, evaluative, expressive that form the basis of the connotative component.
CHARACTERISTIC FEATURES OF THE EMOTIVE ADJECTIVES OF POSITIVE AND NEGATIVE SEMANTICS
Keywords: емосемізм; семантична структура; конотація; експресивність; оцінність; емотивність; емоція; семантика; emotion; emotiveness; semantic structure; connotation; expressiveness; evaluation; semantic structure; semantics; emotive adjective